PEDAGOGICAL CONDITIONS AND EXPERIMENTAL CONCLUSIONS ON THE FORMATION OF MOVEMENT COMPETENCE IN FUTURE HANDBALL COACHES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article presents the theoretical foundations for developing coaches' positive physical-psychological competence in handball teams, highlighting results obtained using various research methods